SYSTEMATIC LITERATUR REVIEW: ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERBASIS LITERASI NUMERASI DI SEKOLAH MENENGAH - Aan Hendrayana; Roudotul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify student errors in solving literacy and numeracy-based mathematics problems at the secondary school level through a literature review of relevant articles. The method employed is a Systematic Literature Review (SLR) involving stages of searching, selection, extraction, and data synthesis. Consequently, 11 articles from the 2022-2026 period were filtered for analysis. The results of the study indicate that student errors predominantly center on the mathematical modeling process. Therefore, instructional strategy interventions that emphasize critical thinking processes and systematic modeling serve as a fundamental solution to improving students' numeracy achievements. The innovation of this research lies in its comprehensive synthesis through a systematic literature review approach that objectively maps students' hierarchical error patterns. This produces functional literacy-based pedagogical strategies that are more specific in mitigating epistemological barriers compared to conventional, theoretical learning approaches